2014
DOI: 10.1136/annrheumdis-2014-205839
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution MRI assessment of dactylitis in psoriatic arthritis shows flexor tendon pulley and sheath-related enthesitis

Abstract: ObjectiveDactylitis is a hallmark of psoriatic arthritis (PsA) where flexor tenosynovitis is common. This study explored the microanatomical basis of dactylitis using high-resolution MRI (hrMRI) to visualise the small entheses around the digits.MethodsTwelve patients with psoriatic dactylitis (4 fingers, 8 toes), and 10 healthy volunteers (6 fingers, 4 toes) had hrMRI of the digits using a ‘microscopy’ coil and contrast enhancement. All structures were evaluated including the tendons and ligaments, related ent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
67
0
8

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(79 citation statements)
references
References 20 publications
4
67
0
8
Order By: Relevance
“…The pathologic process underlying nail involvement in PsA is not well understood and enthesitis is considered as the driver of this involvement. 41 The detailed visualization of the underlying inflammatory patterns at the enthesis (structures typically ,3 mm) was not possible because of the spatial resolution limitations of our system. For tendons (cross-section ,6 mm), we also believe that the reconstructed radiotracer The control ROIs we employed were drawn on the bone.…”
Section: Fluorine-18 Fludeoxyglucose Uptake For the First Carpometacamentioning
confidence: 99%
“…The pathologic process underlying nail involvement in PsA is not well understood and enthesitis is considered as the driver of this involvement. 41 The detailed visualization of the underlying inflammatory patterns at the enthesis (structures typically ,3 mm) was not possible because of the spatial resolution limitations of our system. For tendons (cross-section ,6 mm), we also believe that the reconstructed radiotracer The control ROIs we employed were drawn on the bone.…”
Section: Fluorine-18 Fludeoxyglucose Uptake For the First Carpometacamentioning
confidence: 99%
“…[84,85,93] US Doppler ile konvansiyonel grafideki erozyon progresyonu aras›nda da bir iliflki saptanm›flt›r. [94][95][96][97][98] Ayr›ca US, referans metod olarak MR ile valide edilmifltir. [93] …”
Section: Ultrasonografiunclassified
“…Thus this feature could potentially be a marker of disease severity, affecting the hand function. Recently, Tan et al demonstrated by magnetic resonance imaging (MRI) inflammatory changes at digital pulleys and tendons in dactylitis in PsA patients, suggesting a form of functional enthesitis that could be related to the dactylitis process [19]. Moreover, Tinazzi et al showed pulley thickening in subjects affected by PsA compared with RA and healthy controls [20].…”
Section: Digital Pulleysmentioning
confidence: 99%
“…In imaging studies (US and MRI), soft tissue oedema and flexor tenosynovitis are the two most important elementary lesions described in psoriatic dactylitis [10,19,22]. Overall, oedema of the soft tissues can be interpreted as an inflammation of the "fibrous skeleton" of the digit, which is made up of ligaments, fibrous capsular bands, palmar fasciae, and fibrous sheaths that attach to the bone or dermis [10].…”
Section: Digital Pulleysmentioning
confidence: 99%